Effect of endoscopic third ventriculostomy on cerebrospinal fluid pressure in the cerebral ventricles. (January 2016) - Farnoush, Azadeh; Tan, Kristy; Juge, Lauriane; Bilston, Lynne E.; Cheng, Shaokoon
Abstract: We aimed to show how endoscopic third ventriculostomy (ETV) treatment may affect cerebrospinal fluid (CSF) flow dynamics in hydrocephalus, with and without aqueductal stenosis. Hydrocephalus is a neurological disorder which is characterized by enlarged brain ventricles. The periodic motion of CSF flow as a function of the cardiac cycle was prescribed as the inlet boundary condition at the foramen of Monro, and ETV was modeled as a 5 mm diameter hole in the anterior wall of the third ventricle. The results show that ETV reduces the pressure in the ventricles by nine-fold in the model with aqueductal stenosis, and three-fold in the model without aqueductal stenosis. More importantly, ETV changes the temporal characteristics of the CSF pressure waveform in the model without aqueductal stenosis, such that there is higher pressure in the ventricle during diastole. This study suggests that changes in the temporal characteristics of the CSF pressure waveform in the ventricles may be the reason why ETV treatment is not effective for hydrocephalus without aqueductal stenosis.